(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article examines the psychological and pedagogical aspects of assessing juvenile offenders within the framework of criminal proceedings. It analyzes the legislative and methodological foundations for conducting expert evaluations in cases involving individuals under the age of majority, taking into account the age- related, cognitive, social, and emotional characteristics of adolescents. The author emphasizes the importance of an interdisciplinary approach in the work of professionals-psychologists, educators, and forensic experts—in order to objectively assess developmental levels, personality traits, motivational factors, and conditions of socialization of minors. The article outlines the main criteria for evaluating the behavior and psycho-emotional state of juveniles during the criminal process. The importance of an individualized approach in each case, based on psychological and pedagogical conclusions, is substantiated as essential for the delivery of fair judicial decisions.